Nasoethmoidal meningocele in a child presenting bilateral congenital cystic adenomatoid malformation: Evidence for a new entity or consequence of gestational exposures? - da Rosa, Ernani B.; Silveira, Daniélle B.; Tsugami, Laís G.; Bellé, Nathan L.; Matos, Izabelle O.; Targa, Luciano V.; Betat, Rosilene da S.; da Cunha, André C.; Villacis, Rolando A.R.; Rogatto, Sílvia R. [UNESP]; Dorfman, Luiza E.; Rosa, Rafael F. M.; et al. (Wiley, 2016)
Background: Nasoethmoidal meningocele is considered an uncommon type of cephalocele, and congenital cystic adenomatoid malformation (CCAM) is a rare lung disorder characterized by overgrowth of the terminal bronchioles. Case: We report the unusual association between a nasoethmoidal meningocele and CCAM type II in a fetus exposed to valproic acid and misoprostol. The mother was an 18-year-old woman on her first pregnancy. She had a history of absence seizures since she was 5 years old. She took valproic acid from the beginning of the gestation until the end of the third month. At the end of the third month, she attempted interruption of her pregnancy using misoprostol. The fetal nasoethmoidal meningocele and CCAM type II were identified through morphological ultrasound examination and magnetic resonance imaging. A genome-wide study detected one copy number variation classified as rare, entirely contained into the SPATA5 gene. However, it does not seem to be associated to the clinical findings of the patient. Conclusion: To our knowledge, there is only one case reported in the literature showing the same association between a nasoethmoidal meningocele and CCAM. Thus, the malformations observed in our patient may be related to the gestational exposures. Also, we cannot rule out that the patient may present the same condition characterized by a cephalocele and CCAM described by some authors, or even an undescribed entity, because some hallmark features, such as laryngeal atresia and limb defects, were not observed in our case. Further reports will be very important to better understand the associations described in our study.
Keywords: Congenital cystic adenomatoid malformation; Misoprostol; Nasoethmoidal meningocele; Prenatal diagnosis; Valproic acid